(untitled) (Revista Docentes 2.0, 2024)
In response to the increasing importance of effective online learning strategies, the following study explored the contribution of inferential reading strategies to improving reading comprehension skills within an online learning framework. The research was based on the action research model, using a mixed approach that collects quantitative and qualitative data from four students between 16 and 18 years old who received strategic reading instruction during four sessions. By employing pre- and post-tests along with semi-structured interviews, the study assessed both quantitative and qualitative aspects of participants’ understanding and perceptions. The results indicated a notable improvement in inferential reading comprehension at both the group and individual levels, although with some inconsistencies in performance on specific items. Participants understood learning strategies, inference, and their application in comprehension tasks. Furthermore, the participants’ positive attitudes towards strategy instruction were evident, with many expressing comfort, engagement, and motivation. They particularly emphasized the role of lesson organization, reflection, and feedback in enhancing their comprehension skills. This research underscores the effectiveness of integrating inferential reading strategies in online learning environments, providing valuable insights into student perceptions and the impact of strategy instruction on reading comprehension.